2017
DOI: 10.18203/2319-2003.ijbcp20171110
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of panchgavya GHRIT along with flunarizine in prophylaxis for migraine patients: a comparitive study

Abstract: Background: Propranolol and flunarizine have proven to be useful tools in migraine prophylaxis. This trial aims the comparison of the efficacy of flunarizine, flunarizine and placebo and flunarizine and panchgavya ghrit in migraine prophylaxis.Methods: The present study was a prospective, randomized, open-label, blinded-endpoint trial. Patients with chronic migraine were randomized (1:1:1) to flunarizine and flunarizine and placebo and flunarizine and panchgavya ghrit in three treatment groups. The study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…[ 12 13 ] One clinical trial has included Behavioral Toxicity and Neurological Side effect as assessed by DOTES (Dose recorded and treatment-emergent symptom scale) criteria and found minimal side effects. [ 14 ] No side effects or adverse events were reported in any other studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 12 13 ] One clinical trial has included Behavioral Toxicity and Neurological Side effect as assessed by DOTES (Dose recorded and treatment-emergent symptom scale) criteria and found minimal side effects. [ 14 ] No side effects or adverse events were reported in any other studies.…”
Section: Resultsmentioning
confidence: 99%
“…A lower proportion of patients had Behavioural Toxicity and Neurological Side effects as compared to the Flunarizine-placebo and Flunarizine-only groups. [ 14 ] A study on Shatahvadi taila showed significant improvement in migraine severity, frequency, and duration of attack. [ 24 ] Anutaila nasya, every alternate day for fourteen days, showed good relief in 70% of cases in comparison to 60% of subjects with Kaphaketu rasa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations